The earliest history of the Christian gathering: origin, development, and content of the Christian gathering in the first to third centuries - Alikin, Valerij A. (Vigiliae Christianae, 2010)
Using recent insights into the nature of early Christian communities as religious associations, this book offers a new reconstruction of the origins and development of the weekly Christian gathering and its constitutive elements; based on an analysis of all available evidence from the first three centuries